Diffuse Desquamating Rash Following Exposure to Vancomycin-Impregnated Bone Cement. (August 2014) - Williams, Brett; Hanson, Amy; Sha, Beverly
Objective: To describe a case of systemic desquamating dermatitis following implantation of vancomycin antibiotic–laden cement (ABLC) in a patient with prior history of Stevens-Johnson (SJS) reaction to vancomycin.Case Summary: A 59-year-old man with a history of SJS reaction to systemic vancomycin and recurrent methicillin-susceptible Staphylococcus aureus prosthetic knee infection developed a painful, blistering rash after implantation of bone cement that had been mixed with 2 g of vancomycin. He was started empirically on steroids by his primary care provider and had desquamation about 1 week later.Discussion: Systemic absorption of antibiotics from ABLC has been well documented in the literature. Reports of systemic toxicity are rare, and none have described systemic allergic reactions to vancomycin. This patient's prior episode of SJS was diagnosed at another academic medical center 6 years ago, and records are unavailable. Following low-level reexposure to vancomycin, he developed a diffuse painful desquamating rash. Application of the Naranjo nomogram yielded a score of 8 (probable adverse reaction). Although he did not experience fever, sore throat, or mucous membrane involvement to fulfill classic features of SJS, we believe that his severe rash represented a less-severe form of a systemic hypersensitivity reaction to vancomycin.Conclusion: Antibiotics contained in ABLC are systemically absorbed, though at low levels, and have been associated with systemic toxicities. Antibiotics to which a patient has had a potentially life-threatening reaction should not be used in ABLC. Particular attention should be paid to an individual's antibiotic allergy history prior to implantation of any ABLC.